(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the specifics of the role of strategic management accounting in the process of making effective management decisions at the enterprise in modern conditions. The mechanism of the use of the tools of strategic management accounting by enterprises to ensure the achievement of competitive advantages in the market, as well as to increase the productivity of the management system, is considered. The relationship between strategic management accounting and the process of management decision-making is studied, taking into account that an effective strategic accounting system can become a key factor for successful business development. The main aspects of strategic management accounting are studied, including the definition of strategic goals, the collection and analysis of information, the development of key performance indicators and the identification of strategic alternatives. The influence of modern information technologies on the development of strategic management accounting and the possibilities of their implementation in practice are considered. It was determined that the use of strategic management accounting can provide enterprises with a systematic improvement in the quality of management decisions, reduce risks and increase the efficiency of business processes. The importance of strategic management accounting for ensuring the successful functioning of modern enterprises has been proved, and recommendations for improving this process have been formed. The key aspects of the internal and external environment that affect strategic management accounting are considered, including such factors as changes in legislation, the competitive situation on the market, changes in consumer demands, new technological trends, as well as the mechanism of their influence on the decision-making process and accounting. It was determined that strategic management accounting is a relevant tool for business entities in modern conditions of uncertainty and dynamic changes in the business environment, as it enables enterprises to be flexible and respond to changes in a timely manner, while creating conditions for achieving defined strategic goals. The importance of implementing strategic management accounting in modern business as a key factor in making effective management decisions in order to ensure the sustainable development of enterprises in dynamic conditions of market competition and uncertainty is proven.